2022
DOI: 10.1101/2022.10.12.511960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Border-associated macrophages mediate the neuroinflammatory response in an alpha-synuclein model of Parkinson disease

Abstract: Dopaminergic cell loss due to the accumulation of α-syn is a core feature of PD pathogenesis. Neuroinflammation specifically induced by α-syn has been shown to exacerbate neurodegeneration, yet the role of CNS resident macrophages in this process remains unclear. We found that a specific subset of CNS resident macrophages, border-associated macrophages (BAMs), play an essential role in mediating α-syn related neuroinflammation due to their unique role as the antigen presenting cells necessary to initiate a CD4… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…MRC1 is important for myeloid plasticity and adaptive immune responses 122 , monocytes/BAMs, and, in activated microglia/myeloid cells, can be a marker of activation 123,124 . Significantly, monocytes/BAMs (high expression levels of CD163 and MRC1 ) have recently been shown to be necessary for an alpha-synuclein-induced neurodegeneration in a mouse model of PD 125 . The interaction between T-cells and these monocytes/BAMs via MRC1-PTPRC is consistent with previous reports 5,125 identifying increased colocalization of both cell-types around blood vessels in postmortem PD.…”
Section: Discussionmentioning
confidence: 99%
“…MRC1 is important for myeloid plasticity and adaptive immune responses 122 , monocytes/BAMs, and, in activated microglia/myeloid cells, can be a marker of activation 123,124 . Significantly, monocytes/BAMs (high expression levels of CD163 and MRC1 ) have recently been shown to be necessary for an alpha-synuclein-induced neurodegeneration in a mouse model of PD 125 . The interaction between T-cells and these monocytes/BAMs via MRC1-PTPRC is consistent with previous reports 5,125 identifying increased colocalization of both cell-types around blood vessels in postmortem PD.…”
Section: Discussionmentioning
confidence: 99%
“…The complex and multi-dimensional macrophage response to PFFs and synucleinopathy Macrophages such as microglia can adopt a multitude of states and phenotypes in different neurodegenerative diseases 55 . In PD specifically, several groups have shown that microglia or other CNS-associated macrophages engage in T-cell recruitment 35,56 and inflammasome activation [57][58][59] to drive neurodegeneration. A previous study found upregulation of multiple proinflammatory cytokines in the gut 7 days following PFF injection 18 , suggesting that perhaps ENS macrophages engage a similar pro-inflammatory program to microglia in response to α-syn.…”
Section: Discussionmentioning
confidence: 99%
“…CNS-resident macrophages have been shown to engage in both beneficial and detrimental functions during neurodegenerative diseases and represent promising targets for new therapies [31][32][33] . Prominent examples include activating the adaptive immune response, which can lead to neuronal death [34][35][36] , and microglia-mediated complement-dependent synaptic pruning [37][38][39][40] , which mechanistically links protein aggregates to neuronal dysfunction. Given the range of states macrophages can adopt, and the disease-modifying potential of macrophage phenotype, it is important to elucidate the precise response of ENS macrophages to synucleinopathy and how this response contributes to development and/or progression of the disease process.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting, at this timepoint reduced CD163-immunoreactivity was found in the lesioned hemisphere by IHC. Expression of CD163 in the brain has been associated with border associated macrophages, which have been identified as the driving cells for immune cell recruitment and infiltration (56). Since we only evaluated CD163 expresssion at 8 weeks, it is possible that we missed a significant increase in this glycoprotein.…”
Section: Discussionmentioning
confidence: 99%